1993
DOI: 10.1056/nejm199308053290603
|View full text |Cite
|
Sign up to set email alerts
|

Oral Pilocarpine for Post-Irradiation Xerostomia in Patients with Head and Neck Cancer

Abstract: Pilocarpine improved saliva production and relieved symptoms of xerostomia after irradiation for cancer of the head and neck, with minor side effects that were predominantly limited to sweating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
267
0
9

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(282 citation statements)
references
References 19 publications
2
267
0
9
Order By: Relevance
“…Similar levels of salivary increase have been previously reported in other groups of patients following head and neck irradiation and in patients suffering from Sjögren's syndrome. [19][20][21]23,24 It is noteworthy that we found a similar response to the medication under both resting and stimulated conditions, and for both major salivary glands and whole saliva. Similarly, under resting and stimulated conditions, whole saliva, parotid and SM/SL flow rates increased by 284%, 230% and 200%, and by 242%, 268% and 248%, respectively (P Ͻ 0.01).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Similar levels of salivary increase have been previously reported in other groups of patients following head and neck irradiation and in patients suffering from Sjögren's syndrome. [19][20][21]23,24 It is noteworthy that we found a similar response to the medication under both resting and stimulated conditions, and for both major salivary glands and whole saliva. Similarly, under resting and stimulated conditions, whole saliva, parotid and SM/SL flow rates increased by 284%, 230% and 200%, and by 242%, 268% and 248%, respectively (P Ͻ 0.01).…”
Section: Discussionsupporting
confidence: 70%
“…This extensive response may be attributed to the high dose of pilocarpine hydrochloride administered, the maximal dose recommended in both animal and human studies. [17][18][19][20][21]25,26 Within 2 weeks of drug administration, the subjective xerostomic score was altered to normal. Similar levels of salivary increase have been previously reported in other groups of patients following head and neck irradiation and in patients suffering from Sjögren's syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two placebo-controlled double-blind trials have shown the value of this alkaloid (Johnson et al, 1993;LeVeque et al, 1993). Both multicentre studies were similar in design and contained 207 and 162 patients respectively.…”
Section: Pilocarpinementioning
confidence: 99%
“…Achamos que o principal objetivo deste exame é justamente a comparação entre os resultados pré-e pós-tratamento. Pequenos aumentos da salivação costumam beneficiar substancialmente os pacientes que produziam pouca ou nenhuma saliva, enquanto aumento equivalente em pacientes com maior fluxo salivar pode não desencadear qualquer melhora 26 . Preconizamos também a realização da sialometrias previamente e após procedimentos/ tratamentos que conhecidamente promovem a hipossalivação (ex.…”
Section: Discussionunclassified